Information literacy assessment: Rasch analysis approach - Hani Syazillah, N.; Kaur, K. (2015)
This study aimed to investigate the psychometric properties of adopted and modified the Tool for Real-time Assessment of Information Literacy Skills (TRAILS) using Rasch analysis. The TRAILS assessment is a 25 multiple choice items and was administered to the upper secondary school students. The analysis showed that all items are well-targeted for Malaysian students although some changes need to be done as to include some easier TRAILS. Analysis showed that majority of the students scored over 40% on the IL Assessment. The findings are useful to lead to a new paradigm in assessing competency of IL skills among students using Rasch analysis. The study is hoped to bring a new direction to the process of data analysis in library science research.